Geology of the Kuiper quadrangle (H06), Mercury. Issue 2 (1st December 2022) - Giacomini, L.; Galluzzi, V.; Massironi, M.; Ferranti, L.; Palumbo, P.
ABSTRACT: The Kuiper quadrangle (H06) is located at the equatorial zone of Mercury and encompasses the area between 288°E – 360°E and 22.5°N – 22.5°S. Using the NASA MESSENGER data, we compiled a geological map of the quadrangle at a 1:3, 000, 000 scale. The mapping was mainly based on photo-interpretation of an MDIS (Mercury Dual Imaging System) monochrome 166 m/pixel basemap. Additional datasets were also considered: stereo-DTM of the region, mosaics with high-incidence illumination, and the MDIS global color mosaic. The map shows that the quadrangle is characterized by the prevalence of crater materials which are distinguished into three classes based on their degradation degree. Different plain units were also identified and classified on the basis of their density of cratering. Several structures, mainly represented by contractional faults, were mapped in all quadrangle areas. The map represents the first complete geologic survey of H06 at this scale and provides a highly detailed analysis of the Kuiper quadrangle's surface geology.